Fancy Nancy Explorer Extraordinaire - O'Connor, Jane; Preiss-Glasser, Robin (New York : HarperCollinsPublishers, 2009)
Nancy and her friend Bree explore the fascinating world of birds and insects in their exclusive and glamorous Explorers Extraordinaire Club.
Keywords: Clubs -- Fiction; Insects -- Fiction; Birds -- Fiction; Vocabulary -- Fiction